Events. Issue 142 (November 2015) - Unknown
Abstract : International Policy Governance Association (IPGA) Consultants' Forum An Introductory Training in Policy Governance Annual Private Company Governance Summit International Policy Governance Association (IPGA) 2016 Annual Conference: It's All About Ethics! International Corporate Governance Network Annual Conference BoardSource Holacracy National Coalition for Dialogue & Deliberation (NCDD) Sociocracy/Dynamic Governance